Metagenomic analysis provides insights into functional capacity in a hyperarid desert soil niche community. (10th December 2015) - Vikram, Surendra; Guerrero, Leandro D.; Makhalanyane, Thulani P.; Le, Phuong T.; Seely, Mary; Cowan, Don A.
Summary: In hyperarid ecosystems, macroscopic communities are often restricted to cryptic niches, such as hypoliths (microbial communities found beneath translucent rocks), which are widely distributed in hyperarid desert environments. While hypolithic communities are considered to play a major role in productivity, the functional guilds implicated in these processes remain unclear. Here, we describe the metagenomic sequencing, assembly and analysis of hypolithic microbial communities from the Namib Desert. Taxonomic analyses using Small Subunit phylogenetic markers showed that bacterial phylotypes (93%) dominated the communities, with relatively small proportions of archaea (0.43%) and fungi (5.6%). Refseq‐viral database analysis showed the presence of double stranded DNA viruses (7.8% contigs), dominated by Caudovirales (59.2%). Analysis of functional genes and metabolic pathways revealed that cyanobacteria were primarily responsible for photosynthesis with the presence of multiple copies of genes for both photosystems I and II, with a smaller but significant fraction of proteobacterial anoxic photosystem II genes. Hypolithons demonstrated an extensive genetic capacity for the degradation of phosphonates and mineralization of organic sulphur. Surprisingly, we were unable to show the presence of genes representative of complete nitrogen cycles. Taken together, our analyses suggest an extensive capacity for carbon, phosphate and sulphate cycling but only limited nitrogen biogeochemistry.